Evaluation of three‐dimensional gel electrophoresis to improve quantitative profiling of complex proteomes. Issue 14 (20th June 2013) - Colignon, Bertrand; Raes, Martine; Dieu, Marc; Delaive, Edouard; Mauro, Sergio
<x xml:space="preserve">Abstract</x> Two‐dimensional remains one of the main experimental approaches in proteome analysis. However, comigration of protein leads to several limitations: lack of accuracy in protein identification, impaired comparative quantification, and PTM detection. We have optimized a third additional step of in‐gel separation to alleviate comigration associated drawbacks. Spot resolution is strikingly improved following this simple and rapid method and the positive impact on protein and peptide identification from MS/MS data, on the analysis of relative changes in protein abundance, and on the detection of PTM is described.